Robust Self-Healing Metallo-Supergels of Folic Acid: Potential Sustainable Gelator for Oilfield Applications - Marzabad, Mahya Asgharian; Chattopadhyay, Subhasis; Hietala, Sami; Nonappa, Nonappa; Marek, Radek; Jurček, Ondřej (Chemistry (Weinheim an der Bergstrasse, Germany), 2025)
The majority of known metallosupramolecular gels are based on carefully designed ligands using extensive chemical synthesis. Their gelation is often limited to a certain specific metal salt. We demonstrate that in the presence of a wide group of metal salts natural and readily available folic acid (FA) can act as a supergelator. We report a systematic investigation of 17 mechanically robust FA-based metallogels at extremely low concentrations (<0.2 wt%). Using oscillatory rheological measurements, we further show that these metallogels undergo rapid recovery and self-healing, recovering up to 95% of their original stiffness within 1 min. Among the metallogels studied, FA-chromium(III) acetate gel (0.4 wt%) displayed the highest stiffness with a storage modulus of 4 kPa. More importantly, the stiffness, recovery, and sol ↔ gel transitions can be readily tuned by changing either the metal salt or the concentration. Using a combination of various analytical methods, we also suggest a structure of self-assembly in the metallogel network. This study defines non-toxic FA as a robust and sustainable building block for metallogels-mechanically tunable, multi-responsive soft materials. Finally, as a proof-of-concept experiment, we demonstrate that the FA-chromium(III) acetate gel can be considered as a potent sustainable gellator for enhanced oil recovery applications.
Keywords: oil mining; gel; rheology; folic acid; supramolecular chemistry; metallogel